Ovarian cancer‐associated mesothelial cells induce acquired platinum‐resistance in peritoneal metastasis via the FN1/Akt signaling pathway. Issue 8 (24th January 2020) - Yoshihara, Masato; Kajiyama, Hiroaki; Yokoi, Akira; Sugiyama, Mai; Koya, Yoshihiro; Yamakita, Yoshihiko; Liu, Wenting; Nakamura, Kae; Moriyama, Yoshinori; Yasui, Hiroaki; Suzuki, Shiro; Yamamoto, Yusuke; et al.
Abstract : Peritoneal dissemination of ovarian cancer (OvCa) arises from the surface of the peritoneum, covered by monolayer of mesothelial cells (MCs). Given that both OvCa cells and MCs are present in the same peritoneal metastatic microenvironment, they may establish cell‐to‐cell crosstalk or phenotypic alterations including the acquisition of platinum‐resistance in OvCa cells. Herein, we report how OvCa‐associated mesothelial cells (OCAMs) induce platinum‐resistance in OvCa cells through direct cell‐to‐cell crosstalk. We evaluated mutual associations between OvCa cells and human primary MCs with in vitro coculturing experimental models and in silico omics data analysis. The role of OCAMs was also investigated using clinical samples and in vivo mice models. Results of in vitro experiments show that mesenchymal transition is induced in OCAMs primarily by TGF‐β1 stimulation. Furthermore, OCAMs influence the behavior of OvCa cells as a component of the tumor microenvironment of peritoneal metastasis. Mechanistically, OCAMs can induce decreased platinum‐sensitivity in OvCa cells via induction of the FN1/Akt signaling pathway via cell‐to‐cell interactions. Histological analysis of OvCa peritoneal metastasis also illustrated FN1 expression in stromal cells that are supposed to originate from MCs. Further, we also confirmed the activation of Akt signaling in OvCa cells in contact with TGF‐β1 stimulated peritoneum, using an in vivo mice model. Our results suggest that the tumor microenvironment, enhanced by direct cell‐to‐cell crosstalk between OvCa cells and OCAMs, induces acquisition of platinum‐resistance in OvCa cells, which may serve as a novel therapeutic target for prevention of OvCa peritoneal dissemination. What's new?: The clinical characteristics of refractory advanced ovarian cancer suggest that the peritoneum acts as an anchoring point for metastatic tumors, enabling persistent ovarian cancer (OvCa) cell survival. This study shows that ovarian cancer‐associated mesothelial cells (OCAMs) and OvCa cells invade the extracellular matrix of the peritoneum. OCAMs were further found to directly influence persistent OvCa cell survival via FN1 signaling. FN1 on the surface of OCAMs induced activation of the Akt signaling pathway, thereby fueling platinum resistance in OvCa cells. The findings highlight the potential for targeting OCAMs as a novel therapeutic strategy for preventing peritoneal dissemination of ovarian cancer.